A narrative review on pathology of amnesia and its relation with cessation (Rukhsah) of performing prayer (Solah) - Ariaff, Muhammad Ammar Adli; Abdul Ghani, Radiah; Che Mohamad, Che Anuar; Ikmal Hisham, Ahmad Irfan (2017)
Background: The low percentage of in-ward patients that performing solah (prayer) during their stay in hospital shows the worrying trend because of the minimal knowledge of rukhsah (concession) in solah during certain illness. One of the illness that is difficult to determine the rukhsah is memory disturbance such as amnesia. Amnesia is the memory impairment whether the inability to retrieve the past memory (retrograde amnesia) or the inability to learn new information (anterograde amnesia). Thus, the aim of this study is to review the pathology of amnesia based on current literature review and to relate with the rukhsah in solah among amnesia patients. In Islam, the principle of applying the rukhsah kept an open concept for the application in most disabilities and handicaps. Therefore, with the general guidelines of rukhsah on solah for ghairu ‘aqil (insane) patients by JAKIM, so, this study can be complement to that guideline in term to propose some guidelines of rukhsah on solah among the muslim amnesia patients.